Chinese herbal medicine and active ingredients for diabetic cardiomyopathy: molecular mechanisms regulating endoplasmic reticulum stress - Ao, Lianjun; Chen, Zhengtao; Yin, Jiacheng; Leng, Yulin; Luo, Yue; Fu, Xiaoxu; Liu, Hanyu; Liu, Xiaoke; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2023)
Background：Diabetic cardiomyopathy (DCM) is one of the serious microvascular complications of diabetes mellitus. It is often associated with clinical manifestations such as arrhythmias and heart failure, and significantly reduces the quality of life and years of survival of patients. Endoplasmic reticulum stress (ERS) is the removal of unfolded and misfolded proteins and is an important mechanism for the maintenance of cellular homeostasis. ERS plays an important role in the pathogenesis of DCM by causing cardiomyocyte apoptosis, insulin resistance, calcium imbalance, myocardial hypertrophy and fibrosis. Targeting ERS is a new direction in the treatment of DCM. A large number of studies have shown that Chinese herbal medicine and active ingredients can significantly improve the clinical outcome of DCM patients through intervention in ERS and effects on myocardial structure and function, which has become one of the hot research directions. Purpose：The aim of this review is to elucidate and summarize the roles and mechanisms of Chinese herbal medicine and active ingredients that have the potential to modulate endoplasmic reticulum stress, thereby contributing to better management of DCM. Methods: Databases such as PubMed, Web of Science, China National Knowledge Internet, and Wanfang Data Knowledge Service Platform were used to search, analyze, and collect literature, in order to review the mechanisms by which phytochemicals inhibit the progression of DCM by targeting the ERS and its key signaling pathways. Keywords used included "diabetic cardiomyopathy" and "endoplasmic reticulum stress". Results: This review found that Chinese herbs and their active ingredients can regulate ERS through IRE1, ATF6, and PERK pathways to reduce cardiomyocyte apoptosis, ameliorate myocardial fibrosis, and attenuate myocardial hypertrophy for the treatment of DCM. Conclusions: A comprehensive source of information on potential ERS inhibitors is provided in this review. The analysis of the literature suggests that Chinese herbal medicine and its active ingredients can be used as potential drug candidates for the treatment of DCM. In short, we cannot ignore the role of traditional Chinese medicine in regulating ERS and treating DCM,and look forward to more research and new drugs to come.